Trend in hospitalizations due to ambulatory care-sensitive conditions in the Federal District - Isabel Pintas Marques Horta; Flávia Reis de Andrade; Lorena da Silva Luz Santos; Naira Pereira de Sousa; Luciano Ramos de Lima; Tania Cristina Morais Santa Bárbara Rehem (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to analyze the trend, according to sex, of Ambulatory Care-Sensitive Conditions in the Primary Health Care of the Federal District, from 2009 to 2019. Methods: ecological trend study using ACSC hospitalization data available in the Hospitalization System of the Single Health System. The Prais-Winsten method was used to calculate the annual rate variation, expressed in percentages. The dependent variable was the logarithm of the rates, and the independent one, the years in the time series. Results: the Federal District registered 2,103,951 general hospitalizations, 16.4% of which were due to Ambulatory Care-Sensitive Conditions. Males had a higher rate of hospitalization in the period, and both sexes showed a stationary trend. Conclusions: the time trend of Ambulatory Care- Sensitive Conditions was stationary, but further studies are necessary regarding primary health care coverage.